Estudo fitoquímico e avaliação da atividade biológica de Tontelea Micrantha Mart. ex Schult. (Celastraceae) - Fernanda Lopes Ferreira (2019)
Phytochemical study and biological evaluation of Tontelea micrantha Mart. ex Schult. (Celastraceae) The phytochemical study of leaves, branches and roots of Tontelea micrantha resulted in the isolation/identification of 31 compounds. Among them 20 are pentacyclic triterpenes: friedelin (TM03), 3β-friedelinol (TM04), 3,4-seco-friedelanoic acid (TM05), 28-hydroxyfriedelan-3-one (TM06), friedelan-3,21-dione (TM13), 21βhydroxyfriedelan-3-one (TM14), 21α-hydroxyfriedelan-3-one (TM15), 30hydroxyfriedelan-3-one (TM16), 3-oxo-friedelan-28-al (TM17), friedel-1-en-3,21-dione (TM18), friedelan-1,3,21-trione (TM19), 3-oxo-friedelan-28-oic acid (TM21), 28,29dihydroxyfriedelan-3-one (TM22), 21α,30-dihydroxyfriedelan-3-one (TM23), 28,30dihydroxyfriedelan-3-one (TM24), tingenin B (TM27), netzahualcoyone (TM28), netzahualcoyondiol (TM29), salaquinone A (TM30) and the orthosphenic acid (TM31). Four flavonoids were also isolated: 3-O-[α-L-rhamnopyranosyl (1 → 2)][α-Lrhamnopyranosyl (1→6)]-β-D-glucopyranoside of quercetin (TM10), rutin (TM11), epiafzelechin-(4β → 8)-epicatechin (TM12) dimer and epicatechin (TM25). In addition, the steroid, β-sitosterol (TM20) and its glycosylated derivative, 3-Oβ -D-glicosil-β-sitosterol (TM08), and a β-di-hydroagarofuran sesquiterpene 2,3,6,15-tetra-acetoxy1,9-dibenzoyloxy-8-oxo-β-agarofuran (TM26) were isolated. A carbohydrate, dulcitol (TM09), a mixture of fatty acids (TM07), the gutta percha (TM01) polymer and squalene (TM02), a precursor of pentacyclic triterpenes, were also isolated. The substances TM18, TM19 e TM26 are new compounds. The study of the biological activity consisted of the evaluation of the antimicrobial activity (antibacterial and antifungal), of the antiviral activity against Zika virus and Mayaro virus, of the cytotoxic activity and the study of the inhibition activity of the cardiac Na+,K+-ATPase enzyme. The methanolic leaf extract showed pronounced anti-MAYV activity. Leaf and branch extracts showed anti-ZIKV activity, with the ethyl acetate and methanolic leaf extracts inhibiting viral penetration at lower concentrations of 15.6 μg/mL. The compounds TM11, TM21, TM25, TM26, TM29 and the seed oil showed moderate cytotoxic activity against the mammary carcinoma cells (MDA-MB-231) and the acute (THP-1) and chronic myeloid leukemia cells (K562).